XV International Symposium on Metastable, Amorphous and Nanostructured Materials 6-10 July 2008, Buenos Aires, Argentina Preface - Audebert, F; Damonte, L; Galano, M (2010)
The December 2009 special issue of Journal of Alloys and Compounds focuses on XV International Symposium on Metastable, Amorphous and Nanostructured Materials (ISMANAM) held on July 6-10, 2009 in Argentina. ISMANAM 2008 had 221 participants from four continents that have contributed to the symposium with 267 works. The symposium discussed metals, ceramics, polymers, composites, powders to bulk materials, including composites and nanocomposites. The ISMANAM Steering Committee acknowledged the outstanding achievements of a senior and a junior scientist by granting the awards.